Effect of Tea Variety and Oxidation Duration on Oolong Tea Processed at PPTK Gambung Research Center - Mohammad Prasanto Bimantio; Hilman Maulana; Dika Aristian (International Journal of Food Sciences and Nutrition Innovations, 2025)
Background of study: Oolong tea is commonly produced from Camellia sinensis leaves, while the use of assamica variety has been rarely investigated. Differences in varietal composition and oxidation duration may influence chemical and sensory characteristics of oolong tea, particularly antioxidant performance and polyphenol content.Aims and scope of paper: This study examined how tea variety and oxidation time affect moisture content, polyphenols, antioxidant activity, and sensory properties of oolong tea. The scope included physicochemical and organoleptic evaluation to determine processing conditions that optimize functional quality.Methods: A randomized block design with two factors was applied, namely variety (sinensis and assamica) and oxidation duration (15, 25, and 60 minutes), each with four replications. Measurements included moisture, polyphenols, antioxidant activity using DPPH, and sensory evaluation of color, aroma, and taste.Result: Variety significantly affected moisture, polyphenols, and antioxidant activity, while sensory differences were observed only in color. Oxidation time significantly influenced antioxidant activity but not moisture or polyphenols. The highest antioxidant activity occurred in assamica at 15 minutes, whereas longer oxidation reduced antioxidant levels.Conclusion: The assamica variety produced higher polyphenol and antioxidant values than sinensis. Shorter oxidation preserved antioxidant activity, indicating that combining appropriate variety selection with controlled oxidation may enhance the functional attributes of oolong tea.